Preparation and application of plastic alloy filter based on high-efficiency filtration of rural domestic sewage

By using glass fiber modified nylon 66 and AES resin plastic alloy and spiral curved structure design, the problems of easy wear and corrosion of all-plastic combined filters in wet monsoon climate areas are solved, and the efficient, wear-resistant and weather-resistant rural domestic sewage irrigation filtration effect is achieved.

CN117700987BActive Publication Date: 2025-04-01INST OF BOTANY JIANGSU PROVINCE & CHINESE ACADEMY OF SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311693072.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-11
Publication Date
2025-04-01
Estimated Expiration
2043-12-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively use all-plastic combined filters in humid monsoon climate areas, and steel filters are prone to corrosion and have low production efficiency, which cannot meet the needs of rural domestic sewage irrigation.

Method used

Using a plastic alloy including glass fiber modified nylon 66 and AES resin, a material with high wear resistance and weather resistance is formed by adding compatibility agents, antioxidants, lubricants, tougheners, ultraviolet absorbers and carbon black masterbatches, and a centrifugal filter with a spiral curved surface structure is designed.

Benefits of technology

It realizes the efficient filtration effect used in humid climates, improves the wear and weather resistance of the filter, extends the service life, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117700987B_ABST
    Figure CN117700987B_ABST
Patent Text Reader

Abstract

The present invention provides the preparation and application of a plastic alloy filter based on efficient filtration of rural domestic sewage, and belongs to the technical field of efficient irrigation and reuse filters for rural domestic sewage. The plastic alloy provided by the present invention includes resin and additives; in terms of mass percentage, the resin includes 5-75% of glass fiber modified nylon 666 and 25-35% of AES resin; the mass content of glass fiber in the glass fiber modified nylon 66 is 30%; in terms of mass percentage of the resin, the additives include: 3-8% of compatibilizer; 0.5-1% of antioxidant; 0.8-3.5% of lubricant; 4-6% of toughening agent; 0.3-0.5% of ultraviolet absorber; and 0.5-1% of carbon black masterbatch. The filter prepared by the plastic alloy of the present invention has good wear resistance and weather resistance under the premise of meeting the water treatment effect, and is suitable for rural domestic sewage irrigation in humid regional climates such as the Chuanchang River Basin in Jiangsu.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-efficiency irrigation reuse filters for rural domestic sewage, and in particular to a plastic alloy and a preparation method and application thereof. Background Art

[0002] In recent years, the use of filters to filter rural domestic sewage and subsequently irrigate farmland with it (i.e., rural domestic sewage irrigation technology) has become a new irrigation method that effectively improves water resource utilization and reduces non-point source pollution. However, water quality issues can easily lead to blockage of water pipes and capillaries. Furthermore, high nitrogen and phosphorus content in water can corrode metal walls, accelerating the aging and damage of irrigation equipment. In humid monsoon climates, characterized by high temperatures and heavy rain in summer and cold, dry winters, rural domestic sewage in these environments has high nitrogen and phosphorus content, as well as high hardness and impurities such as rust, making metal filters even less suitable. Furthermore, steel filters are generally bulky and require high injection molding machine capacity, typically requiring at least 800T to 1000T to produce the components. This leads to high energy consumption, low production efficiency, high mold manufacturing costs, and long processing cycles, which hinder the production of injection molded filters.

[0003] All-plastic composite filters are a new type of water treatment filter material that effectively removes suspended solids, particulate matter, microorganisms, and organic matter from water. Compared to metal filters, they are less susceptible to corrosion. Commonly used all-plastic composite filter substrates include PE (polyethylene), PP (polypropylene), and ABS (a terpolymer of acrylonitrile, butadiene, and styrene).

[0004] However, all-plastic composite filters based on these substrates are not suitable for use in humid climates. For example, the Chuanchang River Basin in Jiangsu Province has a humid monsoon climate, characterized by hot and rainy summers and cold, dry winters. Rural domestic sewage in this area has high nitrogen and phosphorus content, as well as impurities such as high hardness and rust. All-plastic composite filters based on these substrates are prone to wear and tear, and their weather resistance is insufficient, shortening their service life.

[0005] In addition to the base material formula, the structure of the filter also has a direct impact on its filtration performance. Therefore, how to improve the material formula and optimize the filter structure has become the research focus of those skilled in the art. Summary of the Invention

[0006] The purpose of the present invention is to provide a plastic alloy and its preparation method and application. The filter prepared using the plastic alloy of the present invention has good wear resistance and weather resistance while meeting the water treatment effect, and is suitable for rural domestic sewage irrigation in humid regional climates such as the Chuanchang River Basin in Jiangsu.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a plastic alloy comprising a resin and an additive;

[0009] Calculated by mass percentage, the resin includes 5-75% of glass fiber modified nylon 666 and 25-35% of AES resin; the mass content of glass fiber in the glass fiber modified nylon 66 is 30%;

[0010] In terms of mass percentage of the resin, the auxiliary agent includes:

[0011]

[0012] Preferably, the compatibilizer is maleic anhydride diluted with styrene; the mass content of maleic anhydride in the compatibilizer is 6%.

[0013] Preferably, the toughening agent includes DuPont N493.

[0014] The present invention provides a method for preparing the plastic alloy described in the above scheme, comprising the following steps:

[0015] Glass fiber modified nylon 66, AES resin, compatibilizer, antioxidant, lubricant, toughening agent, ultraviolet absorber and carbon black masterbatch are mixed and extruded into granules to obtain the plastic alloy.

[0016] Preferably, the extrusion granulation is carried out in a twin-screw extruder, the extrusion temperature is 230-285°C, the aspect ratio of the screw is 30-50, the screw speed is 320-480r / min, and the vacuum pump on the extruder controls the vacuum degree in the extruder to be higher than 0.04MPa.

[0017] Preferably, before the mixing, the glass fiber modified nylon 66 and the AES resin are dried.

[0018] The present invention provides the use of the plastic alloy described in the above scheme or the plastic alloy prepared by the preparation method described in the above scheme in preparing a filter.

[0019] The present invention provides a centrifugal filter, which is prepared from the plastic alloy described in the above scheme or the plastic alloy prepared by the preparation method described in the above scheme. The water inlet of the centrifugal filter is a spiral surface structure.

[0020] Preferably, the cone angle of the centrifugal filter is 10°.

[0021] Preferably, the main diameter of the centrifugal filter is 250 mm.

[0022] The invention provides a plastic alloy, comprising a resin and an additive. Calculated by weight percentage, the resin comprises 5-75% of glass fiber-modified nylon 666 and 25-35% of AES resin. The mass content of glass fiber in the glass fiber-modified nylon 66 is 30%. Calculated by weight percentage of the resin, the additive comprises: 3-8% of a compatibilizer; 0.5-1% of an antioxidant; 0.8-3.5% of a lubricant; 4-6% of a toughening agent; 0.3-0.5% of an ultraviolet absorber; and 0.5-1% of a carbon black masterbatch.

[0023] The present invention adds 30% glass fiber to nylon 66, significantly improving its mechanical properties, dimensional stability, heat resistance, and wear resistance. Its fatigue strength is 2.5 times that of unreinforced (unglass-modified) nylon 66, but its weather resistance for outdoor use needs further improvement. AES resin is a copolymer of ethylene propylene diene monomer (EPDM) grafted with styrene and acrylonitrile. The rubber phase uses EPDM, a highly weather-resistant tertiary ethylene propylene diene monomer (EPDM), which imparts excellent aging resistance to the AES resin. Even without a coating, it maintains its performance even under prolonged exposure to outdoor ultraviolet radiation, rainforest conditions, sunlight, and ozone. Furthermore, AES resin not only exhibits excellent aging resistance, but also, due to the low glass transition temperature of the EPDM rubber phase, exhibits superior low-temperature impact resistance to ABS and AAS resins. The present invention combines the wear resistance of glass fiber reinforced modified nylon 66 with the weather resistance of AES resin, so that the plastic alloy has the advantages of AES resin surface smoothness, high dimensional stability and good weather resistance, and also has the advantages of high heat resistance and wear resistance of glass fiber modified nylon 66.

[0024] The present invention also provides a centrifugal filter made from the plastic alloy described in the above embodiment, wherein the water inlet of the centrifugal filter has a spiral curved surface structure. The centrifugal filter prepared using the plastic alloy not only has excellent wear resistance and weather resistance, but also effectively improves the separation efficiency of the filter by optimizing the water inlet structure, while reducing energy loss at the water inlet and also advantageously lowering pressure drop.

[0025] The results of the examples show that the filter prepared by using the plastic alloy of the present invention has good wear resistance and weather resistance while meeting the water treatment effect, and is suitable for rural domestic sewage irrigation in humid regional climates such as the Chuanchang River Basin in Jiangsu Province. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a preparation flow chart of the plastic alloy of the present invention;

[0027] Figure 2 is the relationship between the running time and the amount of wear;

[0028] Figure 3Flow rate and pressure curves of the centrifugal disc filter made of the plastic alloy of the present invention, the steel filter, and the plastic centrifugal disc filter provided by manufacturer A at an inlet pressure of 0.5 MPa;

[0029] Figure 4 Flow rate and pressure curves of the centrifugal disc filter made of the plastic alloy of the present invention, the steel filter, and the plastic centrifugal disc filter provided by manufacturer A at an inlet pressure of 0.3 MPa;

[0030] Figure 5 Schematic diagram of the centrifugal filter structure; 1- centrifugal filter upper shell, 2- centrifugal tank clamp, 3- O-ring, 4- centrifugal filter lower shell, 5- sealing O-ring, 6- 2.5-inch clamp, 7- sand storage tank clamp, 8- O-ring, 9- sand storage tank body, 10- sand storage tank plug I, 11- sand storage tank support leg, 12- sand storage tank II;

[0031] Figure 6 Schematic diagram of the water inlet structure of the centrifugal filter;

[0032] Figure 7 This is the injection molding process flow chart of the centrifugal filter in Application Example 1;

[0033] Figure 8 Comparison curve of separation efficiency of cone-tube combination structures with different cone angles;

[0034] Figure 9 The pressure drop comparison curves of cone-cylinder combination structures with different cone angles. DETAILED DESCRIPTION

[0035] The present invention provides a plastic alloy comprising a resin and an additive;

[0036] Calculated by mass percentage, the resin includes 5-75% of glass fiber modified nylon 666 and 25-35% of AES resin; the mass content of glass fiber in the glass fiber modified nylon 66 is 30%;

[0037] In terms of mass percentage of the resin, the auxiliary agent includes:

[0038]

[0039] In the present invention, unless otherwise specified, all raw materials used are commercially available products well known in the art.

[0040] The plastic alloy provided by the present invention comprises resin.

[0041] The resin comprises 5-75% by weight, preferably 68-72% by weight, and more preferably 70% by weight, of glass-fiber-modified nylon 66. In the present invention, the glass-fiber content of the glass-fiber-modified nylon 66 is 30% by weight. By adding 30% glass fiber to nylon 66, the mechanical properties, dimensional stability, heat resistance, and wear resistance of nylon 66 are significantly improved, with fatigue strength 2.5 times that of unreinforced (non-glass-fiber-modified) nylon 66.

[0042] The resin comprises 25-30% by mass, preferably 26-29%, and more preferably 27-28% AES resin. AES resin is a copolymer of ethylene propylene diene monomer (EPDM) grafted with styrene and acrylonitrile. The rubber phase utilizes EPDM, a highly weatherable rubber, which imparts excellent aging resistance to the AES resin. Even without a coating, the resin maintains its performance even under prolonged exposure to outdoor UV radiation, rainforest conditions, sunlight, and ozone. Furthermore, AES resin not only exhibits excellent aging resistance, but also exhibits superior low-temperature impact resistance to ABS and AAS resins due to the low glass transition temperature of the EPDM rubber phase.

[0043] In the present invention, the EPDM content in the AES resin is preferably 1-2%, more preferably 1.5%. In an embodiment of the present invention, the AES resin is Kumho HW600 from South Korea. The present invention significantly improves the impact strength of the alloy by blending AES with a high EPDM content with glass-modified nylon 66, demonstrating that the EPDM in the AES resin effectively toughens the glass-modified nylon 66.

[0044] The present invention combines the wear resistance of glass fiber reinforced modified nylon 66 with the weather resistance of AES resin, so that the plastic alloy has the advantages of AES resin surface smoothness, high dimensional stability and good weather resistance, and also has the advantages of high heat resistance and wear resistance of glass fiber modified nylon 66.

[0045] The plastic alloy provided by the invention includes an auxiliary agent.

[0046] In terms of mass percentage of the resin, the additive includes 3-8%, preferably 4-7%, and more preferably 5-6% of a compatibilizer. In the present invention, the compatibilizer is preferably maleic anhydride diluted with styrene; the mass content of maleic anhydride in the compatibilizer is preferably 6%. In the present invention, the compatibility of nylon 66 and AES resin is poor, and direct blending of the two will result in stratification. In the present invention, by adding a compatibilizer, the maleic anhydride in the compatibilizer reacts with the -NH2 group in PA66, thereby allowing the AES resin and glass fiber modified nylon 66 to be reactively expanded, thereby obtaining a plastic alloy with good weather resistance, high dimensional accuracy, and excellent wear resistance.

[0047] The auxiliary agent comprises 0.5-1%, preferably 0.6-0.9%, more preferably 0.7-0.8% of an antioxidant in terms of mass percentage of the resin. In the present invention, the antioxidant preferably comprises antioxidant 1098. In the present invention, the antioxidant is used to prevent oxidation of the plastic alloy.

[0048] The additive comprises 0.8-3.5% of lubricant, preferably 1.0-3.0%, more preferably 1.5-2.5% by mass of the resin. In the present invention, the lubricant is preferably a fatty acid lipid lubricant, more preferably stearic acid monoglyceride, and further preferably PETS (pentaerythritol stearate).

[0049] The auxiliary agent comprises 4-6% of the toughening agent, preferably 4.5-5.5%, more preferably 5%, by mass percentage of the resin. In the present invention, the toughening agent preferably comprises DuPont N493.

[0050] The auxiliary agent comprises 0.3-0.5% of the ultraviolet absorber, preferably 0.35-0.45%, more preferably 0.4%, by weight percentage of the resin. In the present invention, the ultraviolet absorber is preferably ultraviolet absorber UV239.

[0051] The additive comprises 0.5-1% by mass of the resin, preferably 0.6-0.9%, more preferably 0.7-0.8% of carbon black masterbatch. In the present invention, the carbon black masterbatch is used to enhance the material's antioxidant properties while preventing light from penetrating and inhibiting algae growth in sewage.

[0052] The present invention provides a method for preparing the plastic alloy described in the above scheme, comprising the following steps:

[0053] Glass fiber modified nylon 66, AES resin, compatibilizer, antioxidant, lubricant, toughening agent, ultraviolet absorber and carbon black masterbatch are mixed and extruded into granules to obtain the plastic alloy.

[0054] In the present invention, prior to mixing, the glass fiber-modified nylon 66 and AES resin are preferably dried; the drying temperature is preferably 100-120°C, and the drying time is preferably 5-7 hours. In the present invention, the mixing is preferably carried out in a high-speed mixer, and the mixing time is preferably 10-25 minutes.

[0055] In the present invention, the extrusion granulation is preferably carried out in a twin-screw extruder, and the extrusion temperature is preferably 230-285°C, more preferably 240-270°C, and further preferably 250-260°C; the aspect ratio of the screw is preferably 30-50, more preferably 35-45, and further preferably 40; the screw speed is preferably 320-480 r / min, more preferably 350-450 r / min, and further preferably 380-420 r / min; the vacuum degree in the extruder controlled by the vacuum pump on the extruder is preferably higher than 0.04 MPa.

[0056] Figure 1 Be the preparation flow chart of the plastic alloy of the present invention. Figure 1 As shown, the present invention weighs a certain amount of glass fiber modified nylon 66 and AES resin in parts by weight, and the glass fiber modified nylon 66 and AES resin are dried. Then, a certain amount of compatibilizer, antioxidant, lubricant, toughening agent, UV absorber and carbon black masterbatch are weighed in parts by weight, and the mixture and the dried resin are put into a high-speed mixer for stirring. The mixture is discharged and sent to a twin-screw extruder for extrusion and granulation through a metering device. Under the conveying, shearing and mixing of the screw, the materials are melted, compounded, extruded, stretched, cooled and pelletized to obtain a plastic alloy with excellent weather resistance and wear resistance.

[0057] The present invention provides the use of the plastic alloy described in the above scheme or the plastic alloy prepared by the preparation method described in the above scheme in preparing a filter. The present invention has no special requirements for the preparation process of the filter, and a preparation process well known in the art can be used. In the present invention, the filter can be a single filter or a combined filter; the combined filter preferably includes a centrifugal mesh combination filter and a centrifugal laminated combination filter. The filter prepared using the plastic alloy of the present invention has good wear resistance and weather resistance while meeting the water treatment effect, and is suitable for rural domestic sewage irrigation in humid climates such as the Chuanchang River Basin in Jiangsu Province.

[0058] The present invention provides a centrifugal filter, which is prepared from the plastic alloy described in the above scheme. The water inlet of the centrifugal filter is a spiral curved surface structure.

[0059] In the present invention, the components of the centrifugal filter are the same as those of the existing centrifugal filter, and the difference lies only in the local details. In the present invention, the centrifugal filter is mainly composed of an upper shell, a lower shell, a sand storage tank and connecting parts. The upper and lower shells are connected by a clamp, and the clamp further connects the sand storage tank and the centrifugal filter. Its structural diagram is shown as follows Figure 5As shown, among them, 1- centrifugal filter upper shell, 2- centrifugal tank clamp, 3- O-ring, 4- centrifugal filter lower shell, 5- sealing O-ring, 6- 2.5-inch clamp, 7- sand storage tank clamp, 8- O-ring, 9- sand storage tank body, 10- sand storage tank plug I, 11- sand storage tank support leg, 12- sand storage tank II.

[0060] In the present invention, the water inlet of the centrifugal filter is a spiral surface structure, and its structural schematic diagram is as shown in FIG. Figure 6 shown.

[0061] The water inlet structure of a centrifugal filter has an important influence on its separation efficiency and other process indicators. This is mainly because the water inlet controls the flow rate and the resulting inlet flow velocity. The main function of the filter inlet structure is to convert the linear motion of the fluid into high-speed rotational motion, generating a sufficiently large centrifugal force to achieve separation. The inlet structure is designed to be cut-in. The existing water inlet structure is mainly designed to be a simple straight line tangent to the cylindrical body of the centrifugal filter. The disadvantages of this structure are sudden changes, large resistance and easy generation of turbulence, which lead to flow field fluctuations and poor working conditions; at the same time, it also causes excessive energy loss and wear of the wall material near the water inlet. The present invention adopts a progressive curve to replace the ordinary tangential water inlet method. On the one hand, it reduces the turbulence, disturbance and energy loss at the inlet, and is also beneficial to reducing the pressure drop. Moreover, this structure is less affected by the spatial layout and is more suitable for occasions with space restrictions.

[0062] In the present invention, the main diameter of the centrifugal filter (referring to the inner diameter of its cylinder) is preferably 250 mm. The present invention adopts a smaller main diameter of the centrifugal filter to facilitate processing and manufacturing.

[0063] In the present invention, the cone angle of the centrifugal filter is preferably 10°. The size of the filter cone angle not only affects the separation effect of the strong cyclone, but also affects the filtration effect. The present invention designs the cone angle to 10°, which helps to improve the separation efficiency while reducing the pressure drop.

[0064] The present invention has no special requirements for the preparation process of the centrifugal filter. The components are prepared by injection molding and then assembled.

[0065] The plastic alloy provided by the present invention, its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be understood as limiting the scope of protection of the present invention.

[0066] Example 1. Preparation of plastic alloy

[0067] Glass fiber modified nylon 66 was purchased from Dongguan Aoya Plastic Raw Materials Co., Ltd., model PA66 American DuPont 70G33HS1L.

[0068] Glass fiber modified nylon 66 and AES resin were weighed according to Table 1, and the glass fiber modified nylon 66 and AES resin were dried at 100°C for 7 hours. Then, a compatibilizer, an antioxidant, a lubricant, a toughening agent, an ultraviolet absorber and a carbon black masterbatch were weighed according to Table 1, and the mixture was put into a high-speed mixer with the dried resin and stirred for 20 minutes. The mixture was then discharged through a metering device to obtain a mixture, which was fed into a twin-screw extruder for extrusion granulation. Under the conveying, shearing and mixing of the screw, the material was melted, compounded, extruded, stretched, cooled and pelletized to obtain a plastic alloy with excellent weather resistance and wear resistance. The extrusion temperature of the twin-screw extruder was 250°C, the aspect ratio of the screw was 40, the speed of the screw was 400r / min, and the vacuum pump on the extruder controlled the vacuum degree in the extruder to be higher than 0.04MPa.

[0069] Table 1 Example 1 Plastic alloy formula

[0070] Material name Percentage content Glass fiber modified nylon 66 65% AES resin (EPDM content 1.5%) 35% Compatibilizer (styrene-diluted maleic anhydride, maleic anhydride content 6%) 3.0% Antioxidant 1098 0.8% Lubricants (PETS) 1.5% Toughener (DuPont N493) 5% UV absorber UV239 0.4% Carbon black masterbatch 0.8%

[0071] Application Example 1. Preparation of Centrifugal Filters

[0072] The plastic alloy of Example 1 was added to the barrel of an injection molding machine by injection molding process, mixed and then injection molding, shaping, cooling, and drying were performed to make a filter ( Figure 7 The water inlet of the filter is a spiral surface water inlet structure with a main diameter of 250mm and a centrifugal filter cone angle of 10°. The injection molding process is as follows: single mold weight is 160.3g, production specification is 3 inches, and material handle weight is 14.8g; injection molding temperature is five levels of 210℃, 220℃, 210℃, 190℃, and 160℃; injection molding pressure is set at four levels of 80Pa, 80Pa, 70Pa and 60Pa, and the corresponding action time of each pressure is 6.5s, 6.5s, 6.5s and 2.0s respectively; the mold opening process is 4 stages, namely pressure and speed are 65Pa and 10m / s, 40Pa and 15m / s, 40Pa and 20m / s; the mold closing process is set at 3 stages, namely pressure and speed are 50Pa and 40m / s, 30Pa and 20m / s, 100Pa and 30m / s; then one-time demolding and 70s cooling are adopted to obtain an injection molded centrifugal filter with a 3-inch appearance and a main diameter of 250mm.

[0073] Example 2. Determination of the Optimal Cone Angle of a Centrifugal Filter

[0074] The cone angle of the filter refers to the angle of the cone part of the filter. For hydraulic centrifugal filters, the larger the cone angle, the shorter the cone, and the shorter the separation time of the material in it. The processing capacity, separation particle size and separation efficiency are all affected by the length of separation time. In fine particle classification, clarification and desludging operations, separation operations of low density and fine particle size materials, and separation operations of liquid-liquid and ultra-fine materials, small cone angle hydrocyclones (<20°) are used more often. The minimum cone angle is 1.5°; large cone angle hydrocyclones (>20°) are mainly used for coarse particle material classification and sorting operations, and the maximum cone angle is 140°. The size of the cone angle not only affects the separation effect of strong vortex, but also affects the filtration effect. Therefore, the cone angle is an important research parameter, and the embodiments take cone angles of 10°, 15°, and 20° respectively. The separation efficiency comparison curve test of the cone-cylinder combination structure with different cone angles ( Figure 8 ) As can be seen, the separation efficiency and inlet flow rate follow a hump-shaped curve, meaning the curve initially rises, reaches a peak, and then gradually declines. This is primarily due to the strong swirl flow within the hydrocyclone being the primary flow. The curve also shows that a small cone angle significantly impacts separation efficiency. This is because a small cone angle increases the separation space within the cyclone filter, increasing the residence time of the suspension within the filter and thus improving separation efficiency. Comparing various configurations, the 10° cone angle configuration achieves the highest separation efficiency.

[0075] In addition, the pressure drop of the cone-tube combination structure with different cone angles is also different. Figure 9 From the pressure drop comparison curves of the cone-cylinder combination structure with different cone angles, it can be seen that with the increase of the inlet flow rate, the pressure drop increases approximately linearly. This is because the increase in flow rate leads to an increase in the local resistance loss, turbulent energy consumption and friction resistance loss along the way inside the cyclone filter, thereby increasing the energy loss. When the flow rate is the same, the pressure drop of various structures is very small. This is because the parameters selected when designing the centrifugal filter are all within the optimal range of the hydrocyclone. From the perspective of energy conservation analysis, reducing the cone angle will increase the separation space, increase the movement time of the particles in the separator, increase the energy consumed, and therefore increase the pressure drop. It can also be seen from the figure that the pressure drop of the 10° cone angle structure is the largest, especially under large flow conditions. When the flow rate is greater than 50m 3 / h, the pressure drop of each structure is very small, and the relative difference is within 1%.

[0076] It can be seen that the 10° cone angle structure has the highest separation efficiency and the smallest pressure drop, and can be used as the optimal structural size of the cone angle.

[0077] Example 3. Wear resistance test

[0078] Wear resistance indicates a material's ability to resist wear during a specific wear process. In actual wear processes, wear resistance and relative wear resistance are commonly used. Wear resistance is the inverse of a material's wear rate. Its physical meaning is that greater wear resistance indicates a material's strong ability to resist wear, while lower wear resistance indicates a material's weaker ability to resist wear. Therefore, wear resistance is a numerical value that indicates a material's ability to resist wear.

[0079] Filter wear forms are complex and diverse, comprising a combination of surface fatigue, micro-cutting, and corrosive wear. For centrifugal mesh filter combinations, inner wall wear results from a combination of particle impact wear and relative slip between the particles and the wall. Particle size is a key factor influencing inner filter wall wear, determining the forces acting on the particles within the filter, thereby altering their trajectory and concentration distribution. Sand and sediment particles primarily cause localized wear on the inner filter wall, with the most severe wear occurring at the lower end of the filter cone. GB3960-83, "Test Method for Sliding Friction and Wear of Plastics," allows for the determination of the sliding friction and wear properties of plastics and plastic-based composites. However, this sliding friction and wear test does not reflect the localized wear on the lower end of the filter cone caused by water-sand fluids during actual use. Therefore, the wear resistance test presented here primarily measures the wear scar depth at the lower end of the filter cone, simulating actual operating conditions. Wear resistance is assessed based on the wear scar depth.

[0080] Assemble the components of the centrifugal filter according to the drawings and check each handle butterfly valve to ensure it can be fully opened and closed. Use PVC pipes and fittings to connect the water source, centrifugal pump, centrifugal filter (prepared in Application Example 1), water meter, and other components. Pay attention to the direction of water flow from the water meter and centrifugal pump. The centrifugal filter inlet should not be equipped with other components that may affect the straight-end water flow. Use raw tape to seal the threaded connections to ensure that each connection is sealed reliably. After connecting the centrifugal pump, turn on the power to check the motor direction and adjust the phase line so that the water pump rotates in the indicated direction.

[0081] Based on actual usage, the water source was configured with a sand and gravel / water mass ratio of 1:5000 (sand and gravel content of 0.5 g / L), and the sand and gravel particle size was ≤0.5 mm. A plastic centrifugal filter (prepared in Application Example 1) and a steel centrifugal filter were operated simultaneously, and the wear of the two centrifugal filters was tested at the same operating time. The results are shown in Table 2.

[0082] Table 2 Comparison of wear depth between the centrifugal filter of the present invention and the steel centrifugal filter

[0083]

[0084] The changes in the wear depth of the plastic centrifugal filter and the steel centrifugal filter listed in the above table with the operation time are compared and plotted. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that as the operating time increases, the wear loss of both the plastic centrifugal filter of the present invention and the steel centrifugal filter increases, but the wear loss of the steel centrifugal filter increases faster, while the wear loss of the injection molded centrifugal filter of the present invention increases slowly. When the operating time increases from 1 day to 4 days, the wear loss of the steel centrifugal filter is 4 to 6 times that of the injection molded centrifugal filter of the present invention. When the operating time increases from 6 days to 12 days, the wear loss of the steel centrifugal filter is 7 to 9 times that of the injection molded centrifugal filter of the present invention.

[0085] Example 4. Hydrostatic pressure test

[0086] Hydrostatic pressure test at room temperature: The injection-molded centrifugal disc filter (the centrifugal filter of Application Example 1 and the disc filter were combined in series, where the disc filter was also injection-molded from the plastic alloy of Example 1) was tested at a pressure of 2.5 times the rated operating pressure. The normal operating pressure of the injection-molded centrifugal disc filter is 0.4-0.6 MPa, so the test pressure should be 1.5 MPa, i.e., the hydrostatic pressure test pressure is 1.5 MPa. Production inspections are typically conducted at 1.5 MPa for 30 minutes. The centrifugal filter exhibited no leakage, rupture, or deformation. Table 3 shows a comparison of the pressure resistance of conventional steel centrifugal disc filters.

[0087] Table 3 Comparison of centrifugal filter pressure

[0088]

[0089]

[0090] Example 5. Technical index test of injection molded centrifugal laminated filter

[0091] By testing the flow rates of the water inlet and outlet of the injection molded centrifugal laminated filter (as shown in Table 4), it is found that the flow rates meet the flow requirements of the related components supporting it, and its technical indicators are determined to be in compliance with the relevant provisions of the national standards.

[0092] Table 4 Flow rate test of centrifugal laminated filter of the present invention

[0093]

[0094] In order to verify the actual filtration efficiency of this result, under the same pressure conditions, the commonly used steel centrifugal laminated filter in the domestic market (Dayu Water Saving Irrigation Co., Ltd.) and the injection-molded centrifugal laminated filter of manufacturer A (Sijifeng Irrigation Equipment Co., Ltd.) were selected to conduct corresponding flow tests. The test results are shown in Tables 5 and 6:

[0095] Table 5 Flow rate test of steel centrifugal disc filter

[0096]

[0097] Table 6 Flow rate test of manufacturer A plastic centrifugal laminated filter

[0098]

[0099] The flow data of three centrifugal disc filters at inlet pressures of 0.5 MPa and 0.3 MPa are analyzed and curves are drawn, as shown in the figure. Figure 3 and Figure 4 As shown (as Figure 3 The flow pressure curves of the three filters when the inlet pressure is 0.5Mpa and Figure 4 Flow-pressure curves of three filters when the inlet pressure is 0.3Mpa): Through comparative analysis, it can be seen that the pressure-flow curves of the centrifugal laminated filter of the present invention are all above the pressure-flow curves of the other two centrifugal laminated filters, which shows that the filtration performance of the plastic centrifugal laminated filter of the present invention is better than that of the other two centrifugal filters. This is because the injection-molded centrifugal laminated filters are all made by injection molding, with good uniformity and small errors. The injection molding material adopts a carbon fiber-modified nylon 66 composite material and an AES resin blended and modified as the centrifugal filter cone material, which improves the wear resistance and weather resistance of the centrifugal filter cone and solves the problem that the injection molded filter is easy to wear and has poor weather resistance. At the same time, the present invention improves the mechanical properties such as strength and hardness of the injection molded product by optimizing the material ratio parameters and the filter structure, thereby solving the problem of low pressure bearing performance of the injection molded filter and improving the water-sand separation efficiency.

[0100] In addition, under the same inlet pressure, a comparative analysis was conducted on the flow rate average values ​​of the three filters. It can be seen that when the inlet pressure remains unchanged, the average flow rate of the plastic centrifugal laminated filter of the present invention is higher than that of the other two centrifugal laminated filters used for comparison. In addition, combined with the above flow statistics table and pressure-flow curve, it can be seen that the flow range of the plastic centrifugal laminated filter of the present invention under the three water inlet pressure conditions is also wider than that of the other two filters.

[0101] Example 6. Filter separation performance test

[0102] By comparing the separation performance of the injection-molded centrifugal disc filter of the present invention with that of a conventional steel centrifugal disc filter, two sets of centrifugal disc fully automatic filtration systems were installed on the same water inlet pipe, wherein the centrifugal filters were injection-molded parts and steel parts respectively, and the disc filters were of the same specifications. The changes in their respective flow rates and pressure differences, as well as the time interval for backwashing, were observed, and the recorded data are shown in Table 7.

[0103] Table 7 Comparison of separation performance between injection molded centrifugal disc filters and conventional steel centrifugal disc filters

[0104]

[0105] Comparing the data in the table above with the observations, after the automatic backwash differential pressure value is set, the steel centrifugal disc filter reaches the highest differential pressure first. The injection molded centrifugal disc filter has a longer backwash interval and the disc backwash frequency is lower than that of the steel centrifugal filter system. Over the same time period, the changes in differential pressure and flow are not as significant as those of the steel centrifugal filter.

[0106] After the two systems had been operating for a period of time, the water supply was stopped, and the sand storage tanks in the two centrifugal filtration systems were opened. The solid impurities in the sand storage tanks were collected and dried. A mass comparison of the dried solid impurities showed that the weight of the solid impurities in the injection molded centrifugal filter was about 1.4 times that of the solid impurities in the steel centrifugal filter. When screened through a standard sieve with a mesh size of 600μm, the solid impurities in the injection molded centrifugal filter passed through about twice that of the solid impurities in the steel centrifugal filter. When screened through a standard sieve with a mesh size of 300μm, it was found that almost no solid impurities in the steel filter passed through the sieve, but some solid impurities in the injection molded centrifugal laminated filter still passed through the sieve.

[0107] Experimental test results show that, under the same conditions, the injection-molded centrifugal disc filter and the steel centrifugal disc filter can filter solid impurities with a smaller minimum particle size than the steel centrifugal filter, and the number of particles of the same size separated is also greater than that of the steel centrifugal filter. In summary, the injection-molded centrifugal disc filter has a better separation efficiency than the steel centrifugal disc filter. This is because the uniform injection molding of the injection-molded centrifugal discs and the smooth transition of the injection molding angle ensure the stability of the performance. Generally, the inner surface of the centrifugal filter should be smooth, that is, a continuous cone surface without abrupt changes. However, the weld seams, especially the inner surface of the steel centrifugal filter, cannot be polished, which to some extent affects the separation efficiency of the centrifugal filter. At the same time, the size of the filter cone angle and the structure of the water inlet not only affect the separation effect of the strong vortex, but also have an impact on the filtration effect. Through a series of experiments, the present invention selected the optimal cone angle of 10° and improved the water inlet to a spiral surface structure, realizing a progressive spiral surface water inlet method, improving the separation efficiency and achieving efficient water-sand separation.

[0108] Example 7. Weather resistance test of injection molded centrifugal disc filter

[0109] The filter weather resistance test is carried out in accordance with SL470-2010 "Basic parameters and technical conditions for irrigation filters" and GBT16422.2-1999 "Plastics laboratory light source exposure test method Part 2: Nitrogen arc lamp".

[0110] In accordance with the inspection requirements of SL 470-2010, "Basic Parameters and Technical Requirements for Irrigation Filters," and GBT 16422.2-1999, "Plastics Laboratory Light Source Exposure Test Methods - Part 2: Nitrogen Arc Lamp," specimens must be prepared for testing. This experiment conducted overall weathering tests. The weathering resistance of the injection-molded centrifugal disc filter of the present invention was compared with that of an injection-molded centrifugal disc filter from manufacturer A (Sijifeng Irrigation Equipment Co., Ltd.). Two complete sets of plastic disc filters were conditioned under the following conditions: 23°C, 50% RH, and stored for at least 88 hours.

[0111] Experimental Conditions: 1. Test Temperature: Because the surface temperature of the specimen is difficult to accurately measure, the black standard temperature (65±3°C) is used as the test temperature. The black standard temperature approximates the temperature of dark specimens with poor thermal conductivity. 2. Test Humidity: The test humidity is (50±5)%. 3. Rainfall Cycle: The rainfall in the test simulates actual rainfall in the atmospheric environment. Rainfall subjects the specimens to alternating hot and cold temperatures and washes away surface stains. Distilled water is used to prevent corrosion of the equipment. The rainfall cycle is 18 minutes ± 0.5 minutes, with a rest period of 102 minutes ± 0.5 minutes between each rainfall.

[0112] Test Procedure: Place the specimen in a xenon lamp weathering chamber, with the specimen free from any applied stress on the specimen holder. Start the chamber, set the test conditions, and record the start time. During the test, regularly observe the specimen and test conditions for changes. Maintain the specified test conditions throughout the test. Table 8 lists the overall hydrostatic pressure test results for the injection-molded centrifugal disc filter of the present invention and the injection-molded centrifugal disc filter of Manufacturer A after undergoing the same aging test in a xenon lamp weathering chamber.

[0113] Table 8 Comparison of pressure bearing results of different centrifugal disc filters after weathering test

[0114]

[0115]

[0116] As shown in Table 8, the injection-molded centrifugal disc filter of the present invention remained intact after 300 hours of aging in a xenon lamp weathering chamber and maintaining a pressure of 1.5 MPa for 30 minutes. However, commercially available injection-molded centrifugal disc filters exhibited deformation and cracking after only 200 hours of testing. The weathering resistance of the injection-molded centrifugal disc filter of the present invention is significantly superior to that of conventional injection-molded centrifugal disc filters.

[0117] Example 8. Field use tracking and comparative test of injection-molded centrifugal laminated filters

[0118] At the same water source (the groundwater in this area has a high sediment content), two batches of centrifugal + laminated filter systems were connected. One batch of centrifugal laminated filters were injection molded parts, and the other batch of centrifugal laminated filters were steel parts. During continuous use, the use of the centrifugal filters was regularly observed and recorded as shown in Table 9:

[0119] Table 9 Field use tracking and comparison of injection molded centrifugal laminated filters

[0120]

[0121]

[0122] According to the comparative analysis of the test results and observation results, as shown in Table 9, the following conclusions can be drawn:

[0123] (1) With the increase of usage time, the degree of wear of the injection molded centrifugal filter is significantly reduced. When the filtration system of the steel centrifugal filter was in continuous operation for 3 months, the inner wall was seriously worn. After 4 months, rust appeared on the surface, the inner wall was seriously worn, and the lower end of the vertebral body was worn through. However, the vertebral body of the injection molded centrifugal filter was worn through after 6 months of testing. Its wear resistance is significantly better than that of the steel centrifugal filter.

[0124] (2) Through field tracking comparative tests, it can be seen that the wear resistance and service life of injection molded centrifugal filters are better than those of steel centrifugal filters.

[0125] Example 9. Comprehensive evaluation of overall performance technology

[0126] In order to conduct a comparative analysis of performance, the performance of three centrifugal disc filters was tested on the same water source, as shown in Table 10:

[0127] Table 10 Performance comparison of three centrifugal filters

[0128]

[0129] A comparative analysis in Table 10 reveals that, under the same water source and pressure differential, the filter system constructed with the present invention requires the longest backwash interval, demonstrating the highest filtration efficiency and less impurities reaching the secondary laminated filter system. Because the materials and formulations used in the present invention have been repeatedly designed and tested, their pressure-bearing performance is higher than that of the previous two centrifugal filters, and their separation efficiency is also superior to the other two filters. This is due to the innovative design of a highly wear-resistant and weather-resistant plastic alloy for injection-molded centrifugal laminations. The invention utilizes a polymer composite material (65-75% PA66 + 30% GF reinforcing resin, 25-35% AES resin, and other additives, including 3-8% compatibilizer, 0.5-1% antioxidant, 0.8-3.5% lubricant, 4-6% toughening agent, 0.3-0.5% UV absorber, and 0.5-1% carbon black masterbatch) through blending and modification. Through repeated testing and research, a formulation system and filter structure with excellent performance and suitable for this production process have been determined. The composite material of PA66 + 30% GF and AES plastics exhibits high wear resistance, resolving the problem of easy wear in injection-molded centrifugal filters. Furthermore, this composite material is water-resistant and resistant to water vapor erosion, making it more corrosion-resistant than steel filter materials and suitable for use in humid climates.

[0130] In summary, the present invention provides a plastic alloy filter that can filter efficiently under humid climate conditions and a preparation method thereof. The developed materials and filters, on the one hand, have the advantages of strong weather resistance, high wear resistance, strong impact resistance, and high pressure bearing capacity, which can greatly improve the separation efficiency of filters in agricultural irrigation systems in humid climate zones, and solve the problems of easy wear and short service life of all-plastic combination filters, easy corrosion of steel filter materials, and unstable filtering effects; on the other hand, the centrifugal filter provided by the present invention is suitable for filtering groundwater and surface water, and can be configured differently or used alone according to different water qualities. It is a key equipment for extending the service life of the sprinkler and ensuring the quality of irrigation and the normal operation of the micro-drip irrigation system. It is beneficial to the development of water-saving irrigation equipment in the direction of lightweight, high-quality, efficient, economical, applicable, environmentally friendly, and energy-saving technical products.

[0131] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A centrifugal filter, characterized in that: Made of plastic alloy; the water inlet of the centrifugal filter is a spiral curved surface structure; the cone angle of the centrifugal filter is 10°; The plastic alloy comprises resin and additives; In terms of mass percentage, the resin includes 65-75% of glass fiber modified nylon 66 and 25-35% of AES resin; the mass content of glass fiber in the glass fiber modified nylon 66 is 30%; the mass content of EPDM in the AES resin is 1-2%; In terms of mass percentage of the resin, the auxiliary agent includes: Compatibilizer 3~8%; Antioxidant 0.5~1%; Lubricant 0.8~3.5%; Toughening agent 4~6%; UV absorber 0.3~0.5%; Carbon black masterbatch 0.5~1%; The compatibilizer is maleic anhydride diluted with styrene; the mass content of maleic anhydride in the compatibilizer is 6%.

2. The centrifugal filter according to claim 1, characterized in that The toughening agent includes DuPont N493.

3. The centrifugal filter according to claim 1 or 2, characterized in that The preparation method of the plastic alloy comprises the following steps: The glass fiber modified nylon 66, AES resin, compatibilizer, antioxidant, lubricant, toughening agent, ultraviolet absorber and carbon black masterbatch are mixed and extruded and granulated to obtain the plastic alloy.

4. The centrifugal filter according to claim 3, characterized in that The extrusion granulation is carried out in a twin-screw extruder, the extrusion temperature is 230-285° C., the aspect ratio of the screw is 30-50, the speed of the screw is 320-480 r / min, and the vacuum pump on the extruder controls the vacuum degree in the extruder to be higher than 0.04 MPa.

5. The centrifugal filter according to claim 3, characterized in that Before the mixing, the glass fiber modified nylon 66 and the AES resin are dried.

6. The centrifugal filter according to claim 1, characterized in that The main diameter of the centrifugal filter is 250 mm.

Citation Information

Patent Citations

  • Centrifugal filter of micro-irrigation device

    CN104258623A

  • PA66-AES (polyamide 66-acrylonitrile-ethylene propylene diene monomer-styrene) composite material and preparation method thereof

    CN107236299A

  • Modified resin for portable seawater filter and preparation method thereof

    CN115703928A

  • Farmland slight irrigation centrifugal type filter

    CN206521285U